2018
DOI: 10.1038/s41598-018-25164-7
|View full text |Cite
|
Sign up to set email alerts
|

Topical pharyngeal anesthesia provides no additional benefit to propofol sedation for esophagogastroduodenoscopy: a randomized controlled double-blinded clinical trial

Abstract: Propofol sedation has been applied during esophagogastroduodenoscopy procedures, but whether topical pharyngeal anesthesia should be administered at the same time has rarely been reported. Our study examined the role of topical pharyngeal anesthesia in sedated endoscopies in a randomized controlled double-blinded clinical trial. A total of 626 patients who underwent sedated esophagogastroduodenoscopy were randomized into the experimental group (n = 313) or the control group (n = 313). The discomfort score, imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…A previous systematic review reported that pharyngeal local anesthesia improved patient tolerance during UGI endoscopy under traditional sedation, such as with midazolam or meperidine 6 . However, previous RCTs showed that local anesthesia did not affect the total propofol dose, or patient responsiveness 32–34 . These differences indicate that depth of sedation with sufficient amnesia may be important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous systematic review reported that pharyngeal local anesthesia improved patient tolerance during UGI endoscopy under traditional sedation, such as with midazolam or meperidine 6 . However, previous RCTs showed that local anesthesia did not affect the total propofol dose, or patient responsiveness 32–34 . These differences indicate that depth of sedation with sufficient amnesia may be important.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, previous RCTs showed that local anesthesia did not affect the total propofol dose, or patient responsiveness. [32][33][34] These differences indicate that depth of sedation with sufficient amnesia may be important. Minimal sedation usually includes intravenous benzodiazepines, and conscious sedation to deep sedation includes high doses of benzodiazepines, or intravenous propofol.…”
Section: Discussionmentioning
confidence: 99%
“…S8). 29,31,32 Moreover, no significant difference between i.v. and topical subgroups was found on subgroup analysis (P¼0.22).…”
Section: Impact Of Lidocaine Application On Patient Satisfactionmentioning
confidence: 89%
“…Six studies involving a total of 948 patients (lidocaine group, n¼473 vs placebo group, n¼475) were available for analysis. 21,25,28,31,32,34 The forest plot demonstrated a lower pain or discomfort score among patients receiving lidocaine than that in those being given placebos (SMD¼À0.47, 95% CI: À0.8 to À0.14, P¼0.005; I 2 ¼73%) (Supplementary Fig. S6).…”
Section: Impact Of Lidocaine Application On Pain or Discomfort Scorementioning
confidence: 97%
See 1 more Smart Citation